Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1021/acscatal.1c04546
|View full text |Cite
|
Sign up to set email alerts
|

The Enantioselective Intermolecular Saegusa Allylation

Abstract: A simple procedure for the intermolecular enantioselective palladium-catalyzed decarboxylative allylation of β-ketoacids is described. This method, inspired by a stoichiometric control experiment performed by Saegusa and co-workers some 40+ years ago, makes use of allyl carbonates as the coupling substrates and enables direct access to α-allylated ketones bearing newly formed quaternary stereocenters. Experiments suggest that the transformation proceeds via an inner-sphere mechanism and not the traditional out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In 2021, Aponick and co-workers reported an enantioselective approach toward the intermolecular Saegusa allylation . The decarboxylative coupling takes place between cyclic β-ketoacids and allyl carbonates leading to α-allylated ketones bearing quaternary stereocenters in the presence of the palladium catalyst.…”
Section: Reaction Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2021, Aponick and co-workers reported an enantioselective approach toward the intermolecular Saegusa allylation . The decarboxylative coupling takes place between cyclic β-ketoacids and allyl carbonates leading to α-allylated ketones bearing quaternary stereocenters in the presence of the palladium catalyst.…”
Section: Reaction Classificationmentioning
confidence: 99%
“…In 2021, Aponick and co-workers reported an enantioselective approach toward the intermolecular Saegusa allylation. 69 The decarboxylative coupling takes place between cyclic β-ketoacids and allyl carbonates leading to α-allylated ketones bearing quaternary stereocenters in the presence of the palladium catalyst. The reaction exhibits high yield and enantioselectivity for the formation of 5-, 6-, and 7-membered cyclic ketones bearing differently substituted α-allylated quaternary centers (Scheme 83).…”
Section: Generation Of Nucleophiles Via Decarboxylationmentioning
confidence: 99%
“…In these substrates, the allyl electrophile is attached to the enolate precursor. Only a handful of intermolecular protocols for Pd-catalyzed AAA have been disclosed (Scheme B) . In 2004, the Stoltz group demonstrated that silyl enol ethers and diallyl carbonates were suitable coupling partners for Pd-catalyzed AAA in the presence of a specialized fluoride source .…”
mentioning
confidence: 99%